Kontaminasi Tembaga pada Mugil dussumieri (Actinopterygii: Mugilidae, Forsskål, 1775) yang Ditangkap di Perairan Semarang, Indonesia - Chrisna Adhi Suryono; Endang Sri Susilo; Aldo Rizqi Arinianzah; Wilis Ari Setyati; Irwani Irwani; Suryono Suryono (Universitas Diponegoro, 2018)
Contamination of Copper in Mugil dussumeri (Actinopterygii: Mugilidae, Forsskål, 1775) which was caught in Semarang waters, Indonesia The marine environment in Semarang waters are highly polluted by heavy metals such as copper (Cu). On the other side, these areas have become producers of fishery commodities such as mullet fish Mugil dussumieri. The aims of this study was to determine the heavy metal content of Cu in mullet fish during wet monsoon (December 2017 and February 2018). Atomic Absorption Spectrophotometer were used to analysis of Cu concentration in marine water and fish meat. The results show that the Cu content in marine water was not detected while in the meat of mullet fish during December 2017 and February 2018 were 0.66 ± 0.07 mg/kg and 0,604 ± 0.217 mg/kg, respectively. The results were still within the quality standard for maximum limit of Cu content allowed in seafood by FAO/WHO. Lingkungan perairan laut di sekitar Semarang berpeluang sangat tinggi untuk terpolusi logam berat tembaga. Di lain sisi perairan ini menjadi daerah produksi perikanan seperti ikan belanak Mugil dussumieri. Tujuan dari penelitian ini adalah untuk mengetahui kandungan logam Cu dalam daging ikan belanak yang ditangkap selama musim penghujan (Desember 2017 dan Februari 2018). Untuk mengetahui konsentrasi Cu dalam air laut dan ikan belanak digunakan Atomic Absorption Spectrophotometer. Hasil penelitian menunjukkan bahwa konsentrasi logam Cu selama bulan Desember 2017 adalah 0.66 ± 0.07/kg dan selama bulan Februari 0,604 ± 0.217 mg/kg, sedangkan konsentrasi Cu dalam air laut tidak terdeteksi. Hasil penelitian dapat disimpulkan bahwa kandungan Cu dalam ikan belanak masih berada pada konsentrasi yang diperbolehkan oleh FAO/WHO.